A 16-year retrospective surveillance report on the pathogenic features and antimicrobial susceptibility of Pseudomonas aeruginosa isolates from FAHJU in Guangzhou representative of Southern China. (September 2017) - Xie, Jinhong; Yang, Ling; Peters, Brian M.; Chen, Lequn; Chen, Dingqiang; Li, Bing; Li, Lin; Yu, Guangchao; Xu, Zhenbo; Shirtliff, Mark E.
Abstract: Pseudomonas aeruginosa is a major pathogen responsible for nosocomial infections. A 16-year retrospective report from 2000 to 2015 was conducted to assess the antimicrobial resistance of P. aeruginosa in Southern China. A total of 1387 P. aeruginosa were collected from inpatients and outpatients. Susceptibility testing results were interpreted according to the Clinical and Laboratory Standards Institute (CLSI, 2015). Piperacillin, piperacillin-tazobactam, ceftazidime, aminoglycosides and carbapenems remained to be active against P. aeruginosa, with resistance rates ranging from 5.6% to 29.7%. Generally, ampicillin, ampicillin-sulbactam, ceftriaxone and trimethoprim-sulfamethoxazole nearly lost the effect on P. aeruginosa, as the resistance rates increase up to 90%. Notably, sputum and blood specimen showed higher resistance rates than other sources in carbapenems, suggesting more caution should be paid on the choice of antibiotic against infections associated with respiratory tract. Highlights: Piperacillin, ceftazidime, aminoglycosides and carbapenems remained to be effective. Ampicillin, ceftriaxone and trimethoprim-sulfamethoxazole nearly lost the effect. Sputum and blood specimen show higher resistance than other source in carbapenems. The resistance rates of inpatients were higher or similar with those of outpatients.